“DEVELOPMENT AND CHARACTERIZATION OF PHYTOSOMES FOR THE TREATMENT OF ANTI-CANCER ACTIVITY BY USING THE Spirulina (Arthospira Plantesis) EXTRACT” - Raju Rathod; Yogesh Chandanshive (International Journal of Antibiotics, 2024)
This study aims to investigate and evaluate spirulina's anticancer properties.The current research is centred on obtaining a Spirulina-containing drug. The goal is to design and create Phytosomes, characterizing them based on relevant and crucial parameters. The process of solvent evaporation was utilized in the creation of Phytosomes. Various parameters such as zeta potential, particle size, infra-red spectral analysis, % drug content, encapsulation efficiency, and % drug release (% DR) were evaluated. The optimized batch SP2 exhibited a zeta potential of -30.2mV and an average particle size of 554.2 nm is considered well-accepted and suitable due to its significant drug release. Notably, the In-Vitro drug release at the 12th hour and % Encapsulation efficiency of the optimized batch SP2 were reported as 90.87% and 90.42%, respectively. The optimized batch (SP2) underwent stability studies and In-Vitro anticancer assessments, confirming its acceptance, suitability, palatability, ease of administration, and overall elegance.
Keywords: Anticancer activity; Optimization; Phytosomes; Solvent Evaporation Method; spirulina; stability study